2022
DOI: 10.3389/fpubh.2022.793673
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional relative poverty of rural older adults in China and the effect of the health poverty alleviation policy

Abstract: IntroductionAlthough, especially in the past decade, poverty measurement approaches have been duly developed in two paths (from unidimensional to multidimensional poverty and from absolute to relative poverty), merely a few studies have focused on the combination of both perspectives. However, with global aging, poverty among older adults simultaneously presents multidimensionality and relativity characteristics. This paper explores a multidimensional relative poverty index (MRPI) relative to the aged group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Studies on MHP have selected indicators of cardiovascular risk, health status, life expectancy, and malnutrition [11,12]. Studies on multidimensional poverty have included indicators of income, health, education, living conditions, social security, and social participation [48][49][50][51]. Nevertheless, a literature analysis and expert consultation revealed that MHP is not the only unhealthy state.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on MHP have selected indicators of cardiovascular risk, health status, life expectancy, and malnutrition [11,12]. Studies on multidimensional poverty have included indicators of income, health, education, living conditions, social security, and social participation [48][49][50][51]. Nevertheless, a literature analysis and expert consultation revealed that MHP is not the only unhealthy state.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] As the age group increased, HPV increased, [ 52 ] whereas the education level acted the opposite. [ 52 , 53 ] A study [ 54 ] showed that household resource endowment and labor force, such as cultivated lands [ 55 ] and livestock raised, will decrease the risk of relative poverty. [ 54 ] Registered poor households and catastrophic medical expenses increased HPV, consistent with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[52,53] A study [54] showed that household resource endowment and labor force, such as cultivated lands [55] and livestock raised, will decrease the risk of relative poverty. [54] Registered poor households and catastrophic medical expenses increased HPV, consistent with a previous study. [16] The number of adults with chronic disease in households was a protective factor in this study, slightly different from our findings.…”
Section: Covariatesmentioning
confidence: 99%
“…Subsequent scholars have expanded the definition of relative poverty and absolute poverty to continuously enrich the theoretical study of multidimensional relative poverty. In analyzing poverty in an aging society, Weihong Zeng defines relative poverty as the relative deprivation of an individual in a certain situation versus the highest situation [ 5 ]. Compared with multidimensional poverty and relative poverty, multidimensional relative poverty reflects the comprehensiveness of multidimensional poverty in measuring poverty from multiple dimensions and highlights the subjectivity of relative poverty in identifying poverty based on the average income level of society [ 6 ].…”
Section: Introductionmentioning
confidence: 99%